DEFENSE MECHANISM OF JERRY SHAW IN D.J.CARUSO'S EAGLE EYE MOVIE (2008): A PSYCHOANALYTIC APPROACH - Akbar, Mochamad Adam Ali (2010)
The research is proposed to analyze a defense mechanism in a movie with the title Eagle Eye with Psychoanalytic Approach. There are two objectives: the first is to analyze the movie in term of structural elements, and the second is to analyze the movie based on Psychoanalytic Approach. This Research is a descriptive qualitative study, using the movie of D.J. Caruso's Eagle Eye as the object of analysis of the style study. There are two kinds of data sources use in this analyzing, namely primary and secondary. The primary data are the movie and script of the movie itself and the secondary data sources are some books, internet and articles related to the subject. The technique of data collection in this research is library research by summarizing, paraphrasing and documenting the data. In analyzing the data, the writer employs descriptive qualitative analysis. The analysis is started by analyzing Jerry Shaw's id, ego, superego, and then his anxiety. For the last, the writer makes an analysis of Jerry Shaw's character using defense mechanism. The outcome of the Research shows that the movie illustrates a defense mechanism of Jerry Shaw in modern world twenty first century. He works as a copy man and ARIIA suddenly comes then Jerry shows his defense to protect himself. Finally, the conclusion of this analysis is that people can do anything to protect their selves and people who they love.